On the issue of the concept of road safety as an object of law enforcement activity of internal affairs bodies (Journal of actual problems of jurisprudence, 2018)
The article analyzes the concept of road safety as an object of law enforcement activity. The author emphasizes that the study of the security of the individual, society, and the state has a theoretical, methodological and applied direction, requiring its comprehension at the certain abstracted level.The analysis that was made it possible to identify such signs of security as: a state in which there is no danger to the individual, society, or state; the result of the process of ensuring the security of the organizational and functional system, characterized by the level of protection of the individual, society, state.Summing up, the author gives an interpretation of the road safetyposition in socio-philosophical thought as a condition in which there is no danger to the individual, society, state, and the result of the process of ensuring security by an organizational and functional system characterized by the sense of personal security. In legal terms, road safety is a state of road traffic provided with a set of legal and organizational measures reflecting the degree of protection of its participants from real and potential threats and their consequences, as well as from the negative impacts of road traffic on the ecological situationand public health.Key words: safety, road safety, public safety, law enforcement object, law enforcement, securitythreats.